Enhanced intrinsic functional connectivity in the visual system of visual artist: Implications for creativity - Hong, Tzu-Yi; Yang, Ching-Ju; Shih, Chung-Heng; Fan, Sheng-Fen; Yeh, Tzu-Chen; Yu, Hsin-Yen; Chen, Li-Fen; Hsieh, Jen-Chuen (Frontiers in Neuroscience, 2023)
Introduction This study sought to elucidate the cognitive traits of visual artists (VAs) from the perspective of visual creativity and the visual system (i.e., the most fundamental neural correlate). Methods We examined the local and long-distance intrinsic functional connectivity (FC) of the visual system to unravel changes in brain traits among VAs. Twenty-seven university students majoring in visual arts and 27 non-artist controls were enrolled. Results VAs presented enhanced local FC in the right superior parietal lobule, right precuneus, left inferior temporal gyrus (ITG), left superior parietal lobule, left angular gyrus, and left middle occipital gyrus. VAs also presented enhanced FC with the ITG that targeted the visual area (occipital gyrus and cuneus), which appears to be associated with visual creativity. Discussion The visual creativity of VAs was correlated with strength of intrinsic functional connectivity in the visual system. Learning-induced neuroplasticity as a trait change observed in VAs can be attributed to the macroscopic consolidation of consociated neural circuits that are engaged over long-term training in the visual arts and aesthetic experience. The consolidated network can be regarded as virtuoso-specific neural fingerprint.